Osteoconductivity and Hydrophilicity of TiO2 Coatings on Ti Substrates Prepared by Different Oxidizing Processes - Dai Yamamoto; Ikki Kawai; Kensuke Kuroda; Ryoichi Ichino; Masazumi Okido; Azusa Seki (Bioinorganic Chemistry and Applications)
Various techniques for forming TiO2 coatings on Ti have been investigated for the improvement of the osteoconductivity of Ti implants. However, it is not clear how the oxidizing process affects this osteoconductivity. In this study, TiO2 coatings were prepared using the following three processes: anodizing in 0.1 M H3PO4 or 0.1 M NaOH aqueous solution; thermal oxidation at 673 K for 2 h in air; and a two-step process of anodizing followed by thermal oxidation. The oxide coatings were evaluated using SEM, XRD, and XPS. The water contact angle on the TiO2 coatings was measured as a surface property. The osteoconductivity of these samples was evaluated by measuring the contact ratio of formed hard tissue on the implanted samples (defined as the RB-I value) after 14 d implantation in rats' tibias. Anatase was formed by anodizing and rutile by thermal oxidation, but the difference in the TiO2 crystal structure did not influence the osteoconductivity. Anodized TiO2 coatings were hydrophilic, but thermally oxidized TiO2 coatings were less hydrophilic than anodized TiO2 coatings because they lacked in surface OH groups. The TiO2 coating process using anodizing without thermal oxidation gave effective improvement of the osteoconductivity of Ti samples.